Expression of anti-apoptothic protein survinin and its gene BIRC5 in primary breast carcinoma as a prognostic factor for the disease - E. A. Shlyakhtunov (ABV-press, 2019)
Objective: to study the expression of anti-apoptotic protein survivin and its gene BIRC5 in primary breast carcinoma as a potential predictive and prognostic marker.Materials and methods. Using immunohistochemical methods and real-time polymerase chain reaction 67 samples (biopsy) of the primary breast carcinoma were studied for the presence of expression of survivin protein and its gene BIRC5.Results. Expression of survivin was determined in 47 (70.15 %) mammary carcinoma samples. Expression of survivin was most often determined in medium and high grade ductal carcinoma (G2-G3), and was associated with lymphovenous stromal invasion in most cases. Expression of survivin protein correlated with the expression of HER2/neu. In 59.6 % of cases survivin was expressed in tumors with a low Ki-67 index. Most often, survivin was expressed in luminal A and luminal B molecular-biological tumor subtypes. Real-time polymerase chain reaction determined the expression of BIRC5 gene in all 67 carcinoma samples. The level of normalized expression of BIRC5 gene significantly moderately correlated with the expression of its product - survivin protein (r = 0.704, p <0.01) and slightly correlated with the expression of oncoprotein HER2/neu (r = -0.285, p <0.05). The median follow-up was 40 months. Overall survival of patients without survivin expression in primary tumor was 100 %, overall survival of patients with survivin expression was 77.16 % (range 74.6-80.1 %) (p = 0.041), relapse-free survival was 100 % and 71.9 % (range 70.1-74.2 %) respectively (p = 0.037). The ratio of progression risks in the survivin expression group was 10.6 (95 % confidence interval 0.85-132.2) (p = 0.041).Conclusion. Expression of the protein survivin and its gene BIRC5 is an independent adverse prognostic factor and can be used as a predictive and prognostic marker.